Political Knowledge and Its Effect on Voting Decisions: Generation Z Viewers of 'Dirty Vote' Documentary - Pamungkas, Yoma Bagus; Yuwanto, Yuwanto; Adnan, Muhammad; Hasfi, Nurul (Universitas Semarang, 2024)
Introduction: The 2024 Indonesian presidential election will see significant Generation Z participation, yet unverified political information may affect their understanding. The documentary ‘Dirty Vote’ has the potential to enhance political knowledge and influence voting decisions, particularly regarding election fraud–a key concern for Generation Z voters who are active digitally but vulnerable to misinformation. Using the Elaboration Likelihood Model (ELM), this study examines how the documentary influences political knowledge, mediates voting decisions, and affects political engagement. The research evaluates whether ‘Dirty Vote’ can effectively enhance political understanding and shape voting choices among Generation Z. Methods: This explanatory quantitative study targets viewers of the ‘Dirty Vote’ documentary on social media. A sample of 384 participants was determined using the Lemeshow formula and non-probability purposive sampling. Data were collected via Google Forms and analyzed using Generalized Structured Component Analysis (GSCA). The ELM theory guided the analysis. Findings: The study found that ‘Dirty Vote’ significantly enhances political knowledge and influences voting decisions among Generation Z. Political knowledge acted as a mediator, strengthening the documentary's impact. The credibility of the documentary’s source also played a key role in how the information was received. These findings suggest that documentaries can be an effective tool for political education, particularly for young voters. Originality: This study provides new insights into the role of documentaries in political education for Generation Z in Semarang, using ELM theory and GSCA to explore media’s impact on political knowledge and behavior.